Microplastic pollution in lakes and lake shoreline sediments - A case study on Lake Bolsena and Lake Chiusi (central Italy) - Fischer, Elke Kerstin; Paglialonga, Lisa; Czech, Elisa; Tamminga, Matthias (Environmental pollution (1987), 2016)
Rivers and effluents have been identified as major pathways for microplastics of terrestrial sources. Moreover, lakes of different dimensions and even in remote locations contain microplastics in striking abundances. This study investigates concentrations of microplastic particles at two lakes in central Italy (Lake Bolsena, Lake Chiusi). A total number of six Manta Trawls have been carried out, two of them one day after heavy winds occurred on Lake Bolsena showing effects on particle distribution of fragments and fibers of varying size categories. Additionally, 36 sediment samples from lakeshores were analyzed for microplastic content. In the surface waters 2.68 to 3.36 particles/m(3) (Lake Chiusi) and 0.82 to 4.42 particles/m(3) (Lake Bolsena) were detected, respectively. Main differences between the lakes are attributed to lake characteristics such as surface and catchment area, depth and the presence of local wind patterns and tide range at Lake Bolsena. An event of heavy winds and moderate rainfall prior to one sampling led to an increase of concentrations at Lake Bolsena which is most probable related to lateral land-based and sewage effluent inputs. The abundances of microplastic particles in sediments vary from mean values of 112 (Lake Bolsena) to 234 particles/kg dry weight (Lake Chiusi). Lake Chiusi results reveal elevated fiber concentrations compared to those of Lake Bolsena what might be a result of higher organic content and a shift in grain size distribution towards the silt and clay fraction at the shallow and highly eutrophic Lake Chiusi. The distribution of particles along different beach levels revealed no significant differences.
Keywords: chemické látky znečišťující vodu; Plastics; Environmental Monitoring; Geologic Sediments; Wind; Water Pollutants, Chemical; plastické hmoty; vítr; Italy; geologické sedimenty; Particle Size; Particulate Matter; pevné částice; Itálie; monitorování životního prostředí; velikost částic; jezera; Lakes